The Latinist : a novel - Prins, Mark (W.W. Norton & Company, 2022)
"In this wickedly sharp, propulsive debut, a classicist must outmaneuver her manipulative mentor. Tessa Templeton has thrived at Oxford University, under the tutelage and praise of esteemed classics professor Christopher Eccles. Yet shortly before her thesis defense, Tessa learns that Chris has sabotaged her career-and realizes their relationship is not at all what she believed. Driven by what he mistakes as love for Tessa, Chris has ensured that no other institution will offer her a position, keeping her at Oxford with him. His tactics grow more invasive as he determines to prove he has her best interests at heart. Meanwhile, Tessa scrambles to undo the damage, and makes a startling discovery about an obscure 2nd century Latin poet that could launch her into academic stardom, finally freeing her from his influence. A contemporary reimagining of the Daphne and Apollo myth, The Latinist is a page-turning exploration of power, ambition, and the intertwining of love and obsession"--